Avaliação cromática de três marcas comerciais de dentes artificiais após imersão em alimentos líquidos - Correa, Beatriz Elena Arana (2007)
Discoloration of acrylic resin denture teeth may result in patient dissatisfaction. The purpose of this study was to determine the color stability of three brands of acrylic resin denture teeth (Artplus, Biotone, Trilux) by subjecting them to four liquid foods (coffee, cola, red wine and distilled water). Twenty specimens (upper right central incisor teeth A2 shaded) were used. All specimens were stored in distilled water for 24 h at 37°C. At that time (T0) the color of all specimens was measured with a spectrophotometer (POCKETSPECA Color QA). Specimens were suspended in the liquid foods and after 15-day (T1) and 30-day (T2) periods of immersion the color of the specimens was measured again with the spectrophotometer. Color measurements were recorded using the CIEL*a*b* system with D65 (day light) light. The CIEL*a*b* system for measuring chromaticity was chosen to record color differences because it is well suited for determination of small color differences. Mean ΔE (color changes) values were calculated for each material and compared statistically with a two-way analyses of variance and calculating Tukey intervals at 0.95. In ΔE T0T1 the most severe discoloration was apparent with red wine when compared to the specimens stored in distilled water (P=0.003). In ΔE T0T2 the most staining solution was the red wine. Distilled water was the second staining liquid food which affect all acrylic resin denture teeth (P=0.024) and in the ΔE T1T2 no color differences (P=0.328) were found. The conclusions of this study exhibited the greatest chromatic change in red wine liquid food. The specimens immersed in distilled water exhibited their greatest color change after 24 h and 30 days. In the last period it was not found any differences among brands and liquid foods.